Education and science: modern trends - Iakushev A. N., Romitsina G. A., Silanteva N. A., Suntsov A. P., Gorokhov V. F., Chernopyatov A. M., Koshienko I. V., Ryjkova A. A., Danilenkova V. A., Koroviakovskii D. G., Ponamorenko V. E., Nikitova A. V. (Education and science: modern trends, 2016)
this article discusses one method of cash flow management companies – their prediction on the basis of the trend model. Cash Flow Forecasting provides the ability to save the daily solvency of the enterprise, to extract additional profit at the expense of emerging investment of temporarily free financial resources.
Keywords: прибыль; финансовая отчетность; рентабельность; финансовый анализ; денежные потоки; оптимизация; экономико-математические методы; корреляция; эффективность управления; profitability; management efficiency; результаты финансовой деятельности предприятия; приток денежных средств; отток денежных средств; остаток денежных средств; прогнозирование денежных средств; трендовая модель; financial analysis; financial results of the company; financial statements; cash flow optimization; economic and mathematical methods; profit; cash flow; cash outflows; cash balance; cash forecasting; correlation; trend model